2013
DOI: 10.5799/ahinjs.01.2013.01.0235
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of stoma-related complications

Abstract: Objective: One of the few factors, that affect life of people have stoma negatively, are complications developing in tissues where placed stomas or near stomas. We aimed to evaluate the stoma practices performed frequently in our clinic.Methods: Between January 2008 and December 2011, the records of 96 patients who had stoma retrospectively. Factors indication for stoma, emergency procedure, preoperative stoma, type of stoma and complications siting recorded.Results: Ninety-six stoma patients were examined. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…4,13,14,15 Most common stoma complications are skin problems, peristomal infection, mucocutaneous separation, stenosis, ischemia, stomal prolapses, parastomal hernia, retraction, anastomosis leakage, and acute renal failure. 13,15,16,17,18,19,20,21,22,23,24 Most common complications following stoma closure are wound site infection, postoperative ileus, and anastomosis leakage. 25 In a multicenter study by Baykara et al 13 stomal/peristomal complications were reported in 248 patients.…”
Section: Quantitative Evaluation Of the Publicationsmentioning
confidence: 99%
“…4,13,14,15 Most common stoma complications are skin problems, peristomal infection, mucocutaneous separation, stenosis, ischemia, stomal prolapses, parastomal hernia, retraction, anastomosis leakage, and acute renal failure. 13,15,16,17,18,19,20,21,22,23,24 Most common complications following stoma closure are wound site infection, postoperative ileus, and anastomosis leakage. 25 In a multicenter study by Baykara et al 13 stomal/peristomal complications were reported in 248 patients.…”
Section: Quantitative Evaluation Of the Publicationsmentioning
confidence: 99%
“…6,7,25,26 Ülkemizde yapılan retrospektif çalışmada da en sık karşılaşılan komplikasyon oranının %63 oranında peristomal cilt irritasyonu olduğu bildirilmektedir. 27 Kolorektal kanserli stoma açılan hastanın ameliyattan sonra stomasının ödemli, pembe ve sağlıklı bir görünümü olduğu gözlenmiştir. Stoma etrafındaki cilt değerlendirilmesinde postoperatif birinci günde REK skoru 0, üçüncü günde iki olarak belirlenmiştir.…”
Section: Discussionunclassified
“…[1,3,9] stoma dermatitis is a condition that affects the comfort of life, but can be life threatened when it is complicated by infection and evisceration. [10] In terms of prevention, colostomy paste, zinc and antifungal creams have been used, and according to our experience, treatment of dermatitis after stomal inflammation is quite hard. For this reason, we think that the wound site should be cleaned and dried frequently before skin inflammation occurs to protect against stomal dermatitis.…”
Section: Discussionmentioning
confidence: 99%